Simulation of the effect of an oil refining project on the water environment using the MIKE 21 model. (February 2018) - Jia, Peng; Wang, Qinggai; Lu, Xuchuan; Zhang, Beibei; Li, Chen; Li, Sa; Li, Shibei; Wang, Yaping
Abstract: A case study of the Caofeidian oil refining project is conducted. A two-dimensional convective dispersion mathematical model is established to simulate the increase in the concentration of pollutants resulting from the wastewater discharge from the Caofeidian oil refining project and to analyze the characteristics of the dispersion of pollutants after wastewater is discharged and the effect of the wastewater discharge on the surrounding sea areas. The results demonstrate the following: (1) The Caofeidian sea area has strong tidal currents, which are significantly affected by the terrain. There are significant differences in the tidal current velocity and the direction between the deep-water areas and the shoals. The direction of the tidal currents in the deep-water areas is essentially parallel to the contour lines of the sea areas. Onshore currents and rip currents submerging the shoals are the dominant currents in the shoals. (2) The pollutant concentration field in the offshore areas changes periodically with the movement of the tidal current. The dilution and dispersion of pollutants are affected by the ocean currents in different tidal periods. The turbulent dispersion of pollutants is the most intense when a neap tide ebbs, followed by when a neap tide rises, when a spring tide ebbs and when a spring tide rises. (3) There are relatively good hydrodynamic conditions near the project's wastewater discharge outlet. Wastewater is well diluted after being discharged. Areas with high concentrations of pollutants are concentrated near the wastewater discharge outlet and the offshore areas. These pollutants migrate southwestward with the flood tidal current and northeastward with the ebb tidal current and have no significant impact on the protection targets in the open sea areas and nearby sea areas. Highlights: Established a 2D mathematical model to simulate the increase of pollutants. Analyzed the characteristics of the pollutants dispersion. Analyzed the effect of the wastewater discharge on the surrounding sea areas.